THE ROLE OF THYROID HORMONES (T3 AND T4) IN THE FEMALE BODY - Kattaxodjayeva Dinara Utkurxodjayevna; Yusupova Madina Baxromovna; Komiljonov Jamshid Omiljonovich (Bright Mind Publishing, 2025)
The work examines the influence of thyroid hormone during pregnancy. It is also shown that non-treatment in time can lead to several diseases, for example, the most common symptoms such as hypothyroidism.
Keywords: Hormone, thyroid gland, hypothyroidism, triiodothyronine, tetraiodothyronine, thyroxine, Hashimoto's thyroiditis, deficiency, iodine.